2016
DOI: 10.1007/s10597-016-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Health Problems Presented to Integrated Pediatric Behavioral Health Clinics: Differences in Urban and Rural Patients

Abstract: Behavioral health diagnoses and service use may differ based on rurality. The purpose of this study was to examine the patterns of mental disorder diagnoses of urban, rural, and remote pediatric populations. This retrospective study used electronic medical records from integrated behavioral health clinics in Nebraska from 2012 to 2013. Bivariate and multivariable models were used to examine the differences in diagnoses. Adolescents with attention deficit and related disorders were more likely to be male, young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Experiencing discrimination was associated with greater depressive symptoms, and living in a disadvantaged neighborhood was associated with an increased risk for anxiety among minority adolescents (Lopez et al, 2016). In more extensive statewide studies, specific internalizing conditions, such as anxiety, depression, and major affective disorder, were common among older and female adolescents (Watanabe-Galloway et al, 2017). Conditions like substance abuse, bullying, and a previous history of suicide ideation were notable mental health risk factors and are described in further detail below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiencing discrimination was associated with greater depressive symptoms, and living in a disadvantaged neighborhood was associated with an increased risk for anxiety among minority adolescents (Lopez et al, 2016). In more extensive statewide studies, specific internalizing conditions, such as anxiety, depression, and major affective disorder, were common among older and female adolescents (Watanabe-Galloway et al, 2017). Conditions like substance abuse, bullying, and a previous history of suicide ideation were notable mental health risk factors and are described in further detail below.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents with attention deficit disorder (ADD) were more likely to come from a rural background. In contrast, adolescents with adjustment, mood, and anxiety disorders predominantly occurred in urban areas (Watanabe-Galloway et al, 2017). This urban–rural disparity in mood disorder trends may occur because urban adolescents are two times more likely to be screened for a mood disorder than their rural counterparts (Sekhar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The methods of classification of rurality were diverse; however, most studies used some variation of a classification system developed for use by national governmental agencies. For example, five of the studies defined rurality by comparing the zip code of residence to a U.S. government rural designation developed by either the U.S. Census Bureau, U.S. Department of Agriculture (USDA), or U.S. Veterans Health Administration (VHA; Abel et al, 2018; Brooks, 2012; Elhai et al, 2004; McCarthy et al, 2012; Watanabe-Galloway et al, 2017). Three studies used the U.S. Census Bureau County level statistics to determine urban/rural areas, and Parikh et al used an assignment for rurality based upon Statistics Canada guidelines for rural strata within Ontario’s 42 Public Health Units.…”
Section: Resultsmentioning
confidence: 99%
“…Disparities based on race and other demographic factors were measured in six of the included studies (35.2%; Lehman et al, 1998; McCarthy et al, 2012; NAMI, n.d.; Onoye et al, 2013; Rost et al, 2011; Weaver, Himle, et al, 2015). Watanabe-Galloway measured differences by rurality and baseline demographics and reported that the percentage of patients covered by Medicaid was highest in rural children (Watanabe-Galloway et al, 2017). Brooks found that rural women veterans were less likely to present to the Veterans Affairs *VA) for women’s specific care and mental health care than urban women (Brooks, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation